Exploring the Association Between Comorbidity Status and Emotional and Behavioral Disorder Risk in Children Following COVID-19 Infection - Basuki Adi, Winengku; Tri Wirasto, Ronny; Sumarni, P; R. Marchira, Carla (Jurnal Psikiatri Surabaya, 2025)
Introduction: The COVID-19 pandemic had a substantial influence on various sides of global livelihoods. It is overbearing to recognize the relationship between short-term COVID-19 infections and ensuing emotional and behavioral symptoms. Nonetheless, the small number of research on long-term impacts of COVID-19 infections, coupled with deficient surveillance, raises concerns. This gap is particularly critical given the potential increase of depression and anxiety, with a 57% surge, and suicidal ideation, which has risen by 31%. Acknowledging the seriousness of the situation is utmost, necessitating combined efforts to address these issues effectively. Methods: This study implements an observational analytical approach engaging a prospective cohort design, without of experimental interventions. Utilizing the Strength and Difficulties Questionnaire (SDQ) to measure the risk of emotional and behavioral disorders linked to comorbidity status. Twenty-nine children were selected as study participants. Data analysis involved chi-square tests and logistic regression, with statistical significance set at p < 0.05. Results: Outcomes indicate that the overall prevalence of difficulties associated with emotional and behavioral risks stands at 48.3%. Emotional symptoms constitute 27.6%, behavioral issues 31%, hyperactivity and peer-related concerns 48.3%, while prosocial behavior is merely 6.9%. The study reveals a notable impact of comorbidity status on the likelihood of emotional problems, recorded at 54.5% (p=0.028, and C=0.426). Conclusions: The presence of comorbidity status enhances the vulnerability to emotional and behavioral disorders among children post-COVID-19 infection. However, statistical significance is observed only in emotional problems. Keywords: Adolescent, Behavior and Emotional problems, Child, Comorbidity.